Evaluation of the impact of Accelerated Reader on English Reading Performance and Behaviours in Chinese Primary Schools – A Pilot Study - Beng Huat See; Fujia Yang* (Trends in Computer Science and Information Technology, 2025)
Abstract This paper reports on the pilot results of the first independent evaluation of Accelerated Reader (AR), an online reading programme, in China. Despite its adoption in over 800 Chinese schools and robust evaluation elsewhere, AR has not been independently assessed in China. The sample included 528 Year 5 and 6 pupils from two public schools in China. The pilot was a cluster randomised control trial, where four classes (195 pupils) were randomised to receive the AR intervention, while seven (333 pupils) followed business-as-usual instruction. The intervention lasted 12-13 weeks, with one session per week. Impact evaluation showed positive effects on English reading outcome (effect size [ES] = +0.27), overall reading habits (ES = +0.14) and attitudes (ES = +0.15), though regression models suggested these may reflect pre-existing differences. Compliance analysis showed that pupils who complied made greater progress than non-compliers (ES = +0.56), highlighting the importance of session completion. Process evaluation reflected large variation in implementation fidelity, driven by teacher experience, classroom management, and technical support. Key challenges included pupils’ limited English proficiency, digital skills, large class sizes, and mismatched book access. Path analysis indicated a small positive indirect impact of reading behaviours on performance, mainly through reading attitudes.